Dividend policy, ownership structure and corporate governance: An empirical analysis of Indonesian firms - Mardani, Ronny Malavia (University of Islam Malang, 2022)
One of the essential aspects of corporate policy is the decision on dividend payments as this dividend policy affects the value of the company. This study aims to determine whether there is a possible association between dividend policy, ownership structure, and corporate governance of Indonesian financial firms. This study offers empirical evidence on the relationship between variables in the context of Indonesia, which is a frontier market. The sample includes financial firms listed on the Indonesia stock exchange during the period between 2011 and 2017. Data analysis techniques were performed by using ordinary least square regression. Based on the result of 242 observed data analyses, it was found that while managerial ownership has no significant but positive effect on the dividend payout ratio, institutional ownership has significant and negative effects on dividend policy for sample firms. This positive relationship reflects that increasing the percentage of managerial ownership at one particular point, will make managers think that there is no longer any benefit in increasing dividend payout. Moreover, the total number of directors has a significant negative effect on dividend payout and the percentages of an independent members of directors have a positive but not significant effect on dividend policy. This result reflects that the independent board has an essential role in directing management to protect stakeholders' interest in the company. The study also reclaimed that dividend policy is positively and significantly influenced by profitability but inversely proportional to capital structure.